Defect in the procedure as a ground for invalidating the public procurement procedure - Magdalena Taraszkiewicz (Prawo Budżetowe Państwa i Samorządu)
Contracting authority in accordance with Art. 255 PPL is obliged to cancel the public procurement procedure in the event of any of the events listed in this provision. This means that the contracting authority's actions should be deprived of any discretion in relation to the institution of invalidation, and the interpretation of the grounds for invalidating the procedure should be carried out strictly, using grammatical and teleological interpretation. However, the interpretation of the premise of Art. 255 point 6 of the Public Procurement Law The aim of this study is to answer the question: What defects in the public procurement procedure constitute grounds for its invalidation?